(x ^ 2 * y ^ 3) ^ (1/2) * (x ^ 2 * y ^ 3) ^ (1/3) = x ^ (a/3), a/2 if the equation above, where a is a constant, is true for all positive values of x and y, what is the value of a ?
Get the answer
Category: biomedicalengineering | Author: Abraham Uilleam
(x+1)^2=0 (x-1)^2=0 (2x-1)^2=0 (2x+3)^2=0 x^2+4x+4=0 x^2-6x+9=0 x^2+6x=-9 x^2-1=0 x^2-4=0 x^2-11=0
(x+4) solve for x: = 2. (1 point) 3 o x = 2 o x= 10 3 2 x = o x= -2
(x+9) (x-9) step-by-step explanation: this expression is in the form a2 ? b2, so use the difference of squares rule to factor the expression: x^2-81=x